Impact of 12 h shift patterns in nursing: A scoping review. Issue 2 (February 2015) - Harris, Ruth; Sims, Sarah; Parr, Jenny; Davies, Nigel
Abstract: Objectives: To provide a comprehensive scoping review of evidence of the impact and effectiveness of 12 h shifts in the international nursing literature, supplemented by a review of evidence in other, non-nursing related industries. Data sources: A search of the academic literature was undertaken in electronic databases (AMED, MEDLINE, CINAHL, PsychInfo, Scopus, HMIC, the Cochrane Library, Business Source Premier, Econ Lit, ASSIA and Social Policy and Practice). Review methods: A total of 158 potentially relevant nursing research papers and reviews were published between 1973 and 2014. Two reviewers independently reviewed the articles, leaving 85 primary research studies and 10 review papers in the nursing field to be included in the scoping review. Thirty-one relevant primary research papers and reviews were also identified in the non-nursing related industries literature. Results: Research into 12 h nursing shifts fell within five broad themes: 'risks to patients', 'patient experience', 'risks to staff', 'staff experience' and 'impact on the organisation of work'. There was inconclusive evidence of the effects of 12 h shift patterns in all five themes, with some studies demonstrating positive impacts and others negative or no impacts. This also mirrors the evidence in other, non-nursing related industries. The quality of research reviewed is generally weak and most studies focus on the risks, experience and work/life balance for staff, with few addressing the impact on patient outcomes and experience of care or work productivity. Conclusions: There is insufficient evidence to justify the widespread implementation or withdrawal of 12 h shifts in nursing. It is not clearly understood where there are real benefits and where there are real and unacceptable risks to patients and staff. More research focusing on the impact of 12 h nursing shifts on patient safety and experience of care and on the long term impact on staff and work organisation is required.